The novel protease inhibitor SRD441 ointment is not effective in the treatment of adult subjects with atopic dermatitis: results of a randomized, vehicle-controlled study - Fölster-Holst, Regina; Reitamo, S.; Yankova, R.; Worm, M.; Kadurina, M.; Thaci, K.; Bieber, T.; Tsankov, N.; Enk, Alexander; Luger, T.; Duffy, M.; Tansley, R. (Allergy, 2010)
To cite this article: Foelster Holst R, Reitamo S, Yankova R, Worm M, Kadurina M, Thaci K, Bieber T, Tsankov N, Enk A, Luger T, Duffy M, Tansley R. The novel protease inhibitor SRD441 ointment is not effective in the treatment of adult subjects with atopic dermatitis: results of a randomized, vehicle-controlled study. Allergy 2010; 65: 1594-1599. Abstract Background: There is evidence that excessive protease activity in the skin is an important factor in the development of atopic dermatitis. SRD44 is a topically formulated novel protease inhibitor that selectively inhibits Staphylococcal-derived aureolysin and matrix metalloproteinases (MMPs). Methods: This was a double-blind, vehicle-controlled randomized trial conducted in thirteen hospital dermatology outpatient clinics in Germany (9), Bulgaria (3) and Finland (1). Ninety-three out of 103 screened adult subjects with confirmed atopic dermatitis affecting ≤20% of body surface area, with an IGA score of 2 or 3 at randomization were randomized following a washout period to either SRD441 ointment or matching vehicle twice daily for 28 days. The primary efficacy endpoint was the clearance of Atopic dermatitis (AD score of 0 or 1 IGA) at Day 21. Secondary endpoints included measures of SCORing Atopic Dermatitis, pruritus self-assessment, rescue medication use and occurrence of new exacerbations. A range of safety and tolerance endpoints were included. Results: There were no significant treatment differences in IGA success rates at Day 21 (SRD441 ointment, 11.1%; vehicle ointment, 12.5%; P = 1.000). Evaluation of secondary efficacy variables revealed no clinical or important statistical differences between treatment groups. Eighteen subjects (19.4%) discontinued the study drug because of an AE (seven subjects [15.6%] in the SRD441 group and 11 subjects [22.9%] in the vehicle group). Twenty-seven subjects (60.0%) in the SRD441 group and 34 subjects (70.8%) in the vehicle group reported an adverse event (AE). Conclusions: SRD441 ointment did not demonstrate efficacy in the treatment of atopic dermatitis raising questions on the effectiveness of MMPs as a target for the treatment of atopic dermatitis. NCT00882245.